Remand as a cross-institutional system: examining the process of punishment before conviction - Pelvin, Holly (Canadian journal of criminology and criminal justice, 2019)
Currently in Canada, there are more legally innocent people in custody in provincial/territorial prisons than there are sentenced prisoners. This group, known as remand prisoners, constituted 37% of the total prison population – federal and provincial/territorial – in Canada in 2015. Despite growing public attention and legal awareness of the remand problem, little is known about the human costs of pre-trial detention. I outline some of these costs to individuals through a discussion of three distinctive dimensions of remand imprisonment: arrest, court appearances, and daily life in custody. Based on interviews with 120 remand prisoners (60 male, 60 female) at four maximum-security provincial prisons in Ontario, I demonstrate that the system imposes many punishments on individuals long before – and often in the absence of – conviction. The consequences of remand custody have implications for our understanding of the nature of punishment before conviction and for contemporary legal debates in Canada on the issue of pre-trial credit